Simulation Scenarios for Nursing Educators : Making It Real - Campbell, Suzanne Hetzel; Daley, Karen M. (Springer, 2013)
"This second edition of an acclaimed book for nurse educators provides a practical, step-by-step guide to designing and developing simulation scenarios and integrating them into the nursing curriculum. Based on extensive discussion with contributing authors and new faculty, the text has been updated to include changes in simulation pedagogy since the first edition was published in 2008, and thoroughly reorganized to facilitate greater ease-of-use. Outstanding features include scenarios easily adaptable to the instructor's own lab, and a new section on graduate nursing education and interdisciplinary clinical scenarios. Scenarios are ordered according to their complexity for ease of access"--Page 4 of cover